Applications of single-cell RNA sequencing in atopic dermatitis and psoriasis - Xia, Dengmei; Wang, Yiyi; Xiao, Yue; Li, Wei (Frontiers in Immunology, 2022)
Single-cell RNA sequencing (scRNA-seq) is a novel technology that characterizes molecular heterogeneity at the single-cell level. With the development of more automated, sensitive, and cost-effective single-cell isolation methods, scRNA-seq sensitivity and efficiency have been improved. Technological advances in single-cell provide a deeper understanding of the biological diversity of cells present in tissues including inflammatory skin. New subsets of cells have been discovered among the common inflammatory skin diseases, for example, atopic dermatitis (AD) and psoriasis. The technology has also been used to analyze immune cell distributions and cell-cell communications, shedding new light on the complex interplay of components involved in disease responses. Moreover, scRNA-seq is a promising tool in precision medicine due to its ability to define cell subsets with potential treatment targets and characterize the cell-specific responses to drugs or other stimuli. In this mini-review, we briefly summarize the development of scRNA-seq technologies and discuss the latest findings using scRNA-seq that have substantially improved our knowledge of the mechanisms and targeted therapy in inflammatory skin diseases. Finally, we discuss the limitations and technical problems of the current scRNA-seq technology.